KOMUNIKASI, MOTIVASI DAN BUDAYA TERHADAP KINERJA ORGANISASI IKATAN PELAJAR MUHAMMADIYAH SUMATERA SELATAN - Over Mexi; Ratu Mutialela; Moh Hafizni; Isnawijayani Isnawijayani (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Communication is a human activity to mutually understand or understand a message between the communicator and the communicant. In this world every human being involved in communication. Since they existed, communication is an activity that has been carried out by humans. This study aims to analyze communication, motivation and organizational culture on organizational performance. The type of research used in this research is quantitative. The population and sample of this study used a non-probability sampling technique with a saturated sampling method, where all members of the population were used as samples. Data was collected using a questionnaire method using validity, reliability, normality test, heteroscedasticity test, multicollinearity test and hypothesis testing (t test). The final result of this study shows that there is a correlation between all variables X and Y has a strong relationship, based on the results of hypothesis testing, it shows a positive and significant influence caused by communication, motivation and culture on organizational performance of the South Sumatra Muhammadiyah Student Association for the period 2021-2023.